Anisotropic Lithium Ion Conductivity in Single‐Ion Diblock Copolymer Electrolyte Thin Films. Issue 3 (30th November 2015) - Aissou, Karim; Mumtaz, Muhammad; Usluer, Özlem; Pécastaings, Gilles; Portale, Giuseppe; Fleury, Guillaume; Cloutet, Eric; Hadziioannou, Georges
Abstract : Well‐defined single‐ion diblock copolymers consisting of a Li‐ion conductive poly(styrenesulfonyllithium(trifluoromethylsulfonyl)imide) (PSLiTFSI) block associated with a glassy polystyrene (PS) block have been synthesized via reversible addition fragmentation chain transfer polymerization. Conductivity anisotropy ratio up to 1000 has been achieved from PS‐ b ‐PSLiTFSI thin films by comparing Li‐ion conductivities of out‐of‐plane (aligned) and in‐plane (antialigned) cylinder morphologies at 40 °C. Blending of PS‐ b ‐PSLiTFSI thin films with poly(ethylene oxide) homopolymer (hPEO) enables a substantial improvement of Li‐ion transport within aligned cylindrical domains, since hPEO, preferentially located in PSLiTFSI domains, is an excellent lithium‐solvating material. Results are also compared with unblended and blended PSLiTFSI homopolymer (hPSLiTFSI) homologues, which reveals that ionic conductivity is improved when thin films are nanostructured. Abstract : Conductivity anisotropy ratio up to 1000 has been achieved from single‐ion PS‐ b ‐PSLiTFSI thin films by comparing Li‐ion conductivities of out‐of‐plane (aligned) and inplane (antialigned) cylinder morphologies at 40 °C. Results are also compared with PSLiTFSI homopolymer homologues, which reveal that ionic conductivity is improved when thin films are nanostructured.